Learner autonomy: Moroccan EFL university students beliefs and readiness - Oussou, Said; Kerouad, Smail; Hdii, Saida (Studies in English Language and Education, 2024)
Learner autonomy has attracted considerable scholarly attention in language learning. Research on this concept is abundant and continues to flourish. However, to date, scant attention has been paid to researching autonomy in the Moroccan context. Thus, the present mixed-methods study aimed to partially bridge the gap by investigating university EFL students beliefs and their perceived readiness level of autonomy. For this purpose, both quantitative and qualitative methods were employed to collect data. Questionnaires were administered (n=245), and interviews were conducted with selected participants (n=16). An autonomy scale consisting of five parameters (planning and goal-setting, learners expected teacher roles, learners beliefs and affect management, learners social behaviors, and learners self-assessment and learning strategies) was used to elicit and analyze data. The items that made up the learner autonomy scale were adopted and modified from different influentially existing scales. Three main themes were generated and analyzed in the qualitative strand following thematic analysis procedures. The results demonstrate that most students held positive beliefs towards autonomy and appeared ready to embrace it in their learning journey. Students exhibited a strong inclination towards using English outside the classroom (89.8%), displaying a willingness to take responsibility for their learning (85.3%), and setting learning goals (82%). The qualitative results highlight some aspects, such as participating in content creation within lessons and effectively managing their time. In light of these findings, this study suggests pedagogical implications for EFL teachers to enhance learner autonomy in their classrooms as well as a set of recommendations for future research.